“The Shaping Spirit and Rousseau: Literary Cosmology, Cognition and Culture.” - Sinding, Michael (Northrop Frye 100: A Danubian Perspective., 2014)
Frye’s approach to culture integrates bodily, cognitive, semiotic, social, and historical factors. Yet productive dialogue with other approaches is challenging: sympathizers may get stuck “inside” his capacious thinking, while skeptics remain “outside” – today, typically emphasizing contextual factors shaping cultural texts (e.g., ideology). I explore an integrative approach via Frye’s account of the inversion of the axis mundi. Frye’s principle that thought and meaning are structured by metaphor and narrative is central to cognitive science today (Lakoff and Johnson, Turner, Hogan). Studies of cultural and cognitive change and stability (e.g. Greenblatt, Zunshine) can therefore profit from his vision of intertwined imaginative-cultural processes. Frye sees early cultures as rooted in mythologies (canonical narratives addressing “primary concerns”), which mentally crystallize into cosmologies. These world-pictures are organized by spatial metaphors based on the orientation of the human body (e.g. the axis mundi). Cosmologies become frameworks for later literary and theoretical structures. Changes in cosmology, then, affect all of human experience. The most profound change in Western cultural history was the 18th-century inversion of the axis mundi: the locus of value and power shifted from God (above and outside) to humanity (below and within). To develop this account, I examine how cosmological structures inform Rousseau’s revolutionary early Discourse on the Arts and Sciences (Words 239-43), and therein mediate historical change. I identify key spatial metaphors and myths, and assess how they embody and manipulate “image-schemas” such as the vertical scale (up/down) and container (in/out). Analysis indicates that the language of Rousseau's argument reorganizing the traditional cosmology focuses on the inner/ outer contrast more than on an axial above/ below contrast. Causal relations among souls depend primarily on the attachment or detachment of inner substance to outer surfaces: attached soul-substances get pulled apart, weaken, decline, and dissolve; while the detached soul, contained in and oriented to itself, remains solid (integrity) and (if ordinary) attends to words within, or (if extraordinary) rises up strongly and attaches to great things above and beyond.
Keywords: Northrop Frye; Rousseau; literary cosmology; cultural worldview; conceptual metaphor